A DYNAMICAL MODEL OF COMPUTER VIRUS WITH INFECTIVE EXTERNAL STORAGE DEVICE - Nwaokolo, Martin Afam; Gweryina, Reuben Iortyer; Ogohi, Nissy Ufedo (FUDMA JOURNAL OF SCIENCES, 2024)
A computer virus is a type of malicious software program (“Malware”) that, when executed, replicates itself by modifying other computer programs and inserting its own code. Most of our computer systems, media devices and storages are victims of computer virus. Due to the continuous infections of computer systems, several studies and works are being done on the transmission, dynamics and epidemiology of computer virus. It is a major source of concern due to the importance and necessity of the computer system and the usefulness of the internet. Based on the menace caused by the virus to computers, the researcher decided to carry out this work so as to to investigate the propagation effects of computer viruses with infective external storage media on computer systems. In this work, a mathematical model of a dynamical system of computer virus with an infected external storage media on viral spread is formulated, by extending a four-compartment model proposed by Peng et al, (2013) to five compartments. We computed the reproduction potential, the local and global stability analysis of. Numerical simulation shows that when there is no repair for the exposed computers, the infection rate is high (), but when exposed computers are being repaired, there is reduction in the number of exposed and infected computers).